2021
DOI: 10.1016/j.buildenv.2021.108049
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of particle exposure at different seats in a single-aisle aircraft cabin

Abstract: During the COVID-19 pandemic, exposure to particles exhaled by infected passengers in commercial aircraft cabins has been a great concern. Currently, aircraft cabins adopt mixing ventilation. However, complete mixing may not be achieved, and thus the particle concentration in the respiratory zone may vary from seat to seat in a cabin. To evaluate the particle exposure in a typical single-aisle aircraft cabin, this investigation constructed an aircraft cabin mockup for experimental tests. Particles were release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…Meanwhile, by releasing particles produced by sandalwood combustion rather than real virus‐laden particles, Kong et al 114 evaluated the performance of a ventilation system against the exposure of healthcare workers to SARS‐CoV‐2 through a series of experiments. Li et al 115 sought to analyze the airborne exposure mechanism of the virus in an aircraft cabin experimentally. They evaluated the exposure to virus‐laden particles by releasing DEHS droplets in different locations in the cabin.…”
Section: Studies Of Airborne Covid‐19 Transmission In Indoor Spacesmentioning
confidence: 99%
“…Meanwhile, by releasing particles produced by sandalwood combustion rather than real virus‐laden particles, Kong et al 114 evaluated the performance of a ventilation system against the exposure of healthcare workers to SARS‐CoV‐2 through a series of experiments. Li et al 115 sought to analyze the airborne exposure mechanism of the virus in an aircraft cabin experimentally. They evaluated the exposure to virus‐laden particles by releasing DEHS droplets in different locations in the cabin.…”
Section: Studies Of Airborne Covid‐19 Transmission In Indoor Spacesmentioning
confidence: 99%
“…Therefore, it is necessary to validate the CFD simulation results. Experimental data from Li et al 30 in a single‐aisle aircraft cabin were used for validation in the present study. The data includes distributions of airflow, air temperature, and particle concentration.…”
Section: Validation Of Cfd Modelmentioning
confidence: 99%
“…The two main approaches for studying droplet transmission in an aircraft cabin are experimental measurements and computer simulations. Experimental measurements can provide realistic and reliable information, [29][30][31] but it can be prohibitively expensive to build mockups that represent various aircraft models and to reproduce the distribution of full-size particles. Compared with experimental methods, computational fluid dynamics (CFD) simulations are inexpensive, and aircraft cabin models and boundary conditions can easily be changed in CFD.…”
Section: Simulation Of Sars-cov-2 Transmission In An Aircraft Cabinmentioning
confidence: 99%
See 1 more Smart Citation
“…Beneke et al 146 measured a roughly 37% decrease in particle concentration with each successive row in the longitudinal direction from the source in a cabin mock‐up. In a cross–section with very strong mixing, experimental measurements by Li et al 147 in a cabin mock‐up found that the particle exposure for the passenger in the window seat was always the lowest, regardless of the particle source location. The researchers also found that particles from a passenger can be transported across at least four rows of seats in the longitudinal direction, which was much farther than the distance of two to three rows stated in earlier literature.…”
Section: Efforts To Improve the Cabin Air Environmentmentioning
confidence: 99%